Specific Distribution of GJB2 Mutations in Kurdistan Province of Iran; Report of a Relatively Isolated Population - T. Bahrami; N. Jalilian; G. Karbasi; M. R. Noori- Daloii (Journal of Sciences, Islamic Republic of Iran)
Hearing Loss (HL) represents high genetic heterogeneity with an incidence of almost 1 out of 500 newborns in most populations. Approximately half of the cases have a genetic basis that most of them are autosomal recessive non-syndromic (ARNSHL) with DFNB1-related defect in many worldwide populations. Given the heterogeneity of the trait together with the unique infrastructure of Iranian population, made it necessary to study other loci than GJB2 in various ethnic groups in order to elucidate the genetic etiology of HL in Iran. The present study was designed to determine the contribution of four DFNB loci in Kurdistan Province, west Iran. In this connection, we performed GJB2 analysis and homozygosity mapping using STR markers covering the DFNB21, DFNB4 and DFNB7/11 loci in 20 pedigrees with ARNSHL. GJB2 mutations were the cause of HL in 20% of the patients. However, surprisingly, we only observed 35delG and IVS1+1G>A mutation among the study population.  We also did not find any family linked to DFNB21, DFNB4 and DFNB7/11. Our results indicate the contribution of other loci in etiology of HL in Kurdistan that needs to be carefully investigated.